Prospek Kontrasepsi Pria dalam Pengendalian Pertumbuhan Penduduk melalui Pendekatan Molekular - Putri Rahayu Ratri; Mira Andriani (ARTERI : Jurnal Ilmu Kesehatan, 2020)
Nowadays, developing contraception methods were mostly addressed to women. The development of male contraception was still limited. There were condoms, vasectomies, and interrupted intercourse, which used in male contraception. The condom method and interrupted intercourse have a high failure rate and inconvenience in its use. The vasectomy method is invasive and expensive. The development of molecular-based contraceptive methods with minimal impacts on health is expected to be a good breakthrough in the context of population control and improving the quality of health. The study aims to summarize and analyze the early development of contraception until the invention of molecular contraception through immunologic, proteomic, and metabolomics science. This article review was done by studying literature in the PubMed Central (PMC), Springer, and Open Access ScienceDirect databases. The search was performed with the keywords "Contraception", "Molecular Contraception", "Male Contraception", and "Immunocontraception". Journal articles that fit the theme of the review are then reviewed by paraphrasing the core of the research. The conclusion drawn from the review is that male contraception using the molecular method is still being developed at a pre-clinical experimental stage using animal laboratory technique and in vitro technique. The key to the success of this molecular method is that the more specific the molecular target at male fertility levels, the better of contraceptive effect. The molecular- based contraception is expected to be a breakthrough in terms of population control that have more effective, safe, and comfortable, especially for male contraception